Decentralized planning with an interdependent marketing-production system - Abad, Prakash L.; McMaster University, Faculty of Business (My University, 1980)
An interdependent marketing-production planning model is developed based on control theory. The overall model is a composition of the Vidale-Wolfe model relating advertising rates to sales rates, and the HMMS production/ inventory planning model. Using the overall model as a reference point, it is shown that in certain circumstances a decentralized (separate) marketing production planning process can yield near optimal results. A transfer pricing mechanism provides the best results and several examples are presented to illustrate the cases in which decentralized planning does and does not work well.
24, 4 leaves ; Includes bibliographical references (leaves 22-24). ;
Keywords: Marketing > Management > Mathematical models Production functions (Economic theory) Control theory